Therapeutic benefit of a combined strategy using erythropoietin and endothelial progenitor cells after transient focal cerebral ischemia in rats. (November 2013) - Pellegrini, Lionel; Bennis*, Youssef; Guillet, Benjamin; Velly, Lionel; Garrigue, Philippe; Sabatier, Florence; Dignat-George, Françoise; Bruder, Nicolas; Pisano, Pascale
Abstract : Objective: Many studies have demonstrated beneficial effects of either erythropoietin (EPO) or endothelial progenitor cell (EPC) treatment in cerebral ischemia. To improve post-ischemic tissue repair, we investigated the effect of systemic administration of endothelial colony-forming cells (ECFCs), considered as relevant endothelial progenitors due to their specific vasculogenic activity, in the presence or absence of EPO, on functional recovery, apoptosis, angiogenesis, and neurogenesis in a transient focal cerebral ischemia model in the adult rat. Design: Experimental study. Intervention: The rats were divided into four groups 24 hours after ischemia, , namely control, ECFCs, EPO, and ECFCs+EPO, and received a single intravenous injection of ECFCs (5×10 6 cells) and/or intraperitoneal administration of EPO (2500 UI/kg per day for 3 days). Measurement: Infarct volume, functional recovery, apoptosis, angiogenesis, and neurogenesis were assessed at different time points after ischemia. Main results: The combination of EPO and ECFCs was the only treatment that completely restored neurological function. The ECFCs+EPO treatment was also the most effective to decrease apoptosis and to increase angiogenesis and neurogenesis in the ischemic hemisphere compared to controls and to groups receiving ECFCs or EPO alone. Conclusion: These results suggest that EPO could act in a synergistic way with ECFCs to potentiate their therapeutic benefits.